Uji Aktivitas Anti Aging Sediaan Gel Ekstrak Etanol 70 % Daun Salam (Syzygium polyanthum) - Anik Wahyuni; Wahyu Purwanjani; Supriyanto Purwanjani (Pratama Medika : Jurnal Kesehatan, 2024)
Aging causes the skin to become wrinkled. The cause of aging is free radicals, free radicals in the form of UV-A rays. Bay leaf (Syzygium polyanthum) is a plant that contains flavonoid compounds which can act as antioxidants which can provide anti-aging activity. This test was carried out to find out that bay leaf extract gel was able to provide anti-aging activity. Methodology; The bay leaf extract was tested to be ethanol free and the chemical compound content was identified. The gel preparation was made using bay leaf extract with a concentration of 1.5%, 3%, 4.5%, which was tested for stability including organoleptic test, homogeneity test, pH test, adhesive test, viscosity test, and spreadability test and tested for anti-aging activity. includes percent collagen, percent elasticity, percent moisture.Results; The results of the FI, FII, and FIII gel stability tests meet the requirements for gel preparations including: pH test, viscosity test, adhesion test, and spreadability test. The results of testing the anti-aging activity of the bay leaf extract gel preparation with a concentration of 4.5% provided the most effective anti-aging effect. Conclusion; The results of the FI, FII, and FIII bay leaf extract gel tests had good stability. anti-aging activity test of bay leaf extract gel preparation with a concentration of 4.5% provided the most effective anti-aging effect.